Fundamentals of Islamic money and capital markets - Mohd Azmi Omar; Muhamad Abduh; Raditya Sukmana (Wiley finance series, 2013)
The first comprehensive guide to Islamic financial markets Based on the course taught at the International Islamic University Malaysia, this is the first book on Islamic finance to focus exclusively on money and capital markets